Social journalism: a pending page of the ecuadorian press - Cardoso Milanés, Heriberto; Álvarez Romero, Livinstong Israel (Scripta Mundi, 2022)
This article constitutes an exploratory study of the main manifestations of the so-called “social journalism” nowadays mainly in the Ecuadorian scenario, based on an exhaustive analysis of some of its theoretical approaches and the international and national context that may be affecting growth of this “journalistic specialization”. Hence its focus on the increase in violence in all its manifestations, from domestic to the tensions caused by wars at the international level, as well as the development of pandemics, inequality, discrimination, hunger, misery, unemployment and neoliberal tendencies, to the privatization of education, health and social security; to which are added natural disasters and climate change with its incidence in droughts, floods and earthquakes. A large part of these issues, often picked up by the mainstream press from the show and the exploitation of their emotional angles, are undoubtedly beginning to have a massive expression through the internet social media and often on the lips of their own protagonists, both individuals as well as non-governmental institutions with their respective spaces on WEB pages. As for the methodology used for this article, a documentary and bibliographic analysis was used as one of the main techniques, including the review of randomly selected content in a large-circulation Ecuadorian newspaper and a TV channel, as well as from various websites focused on these topics.